“The impact of motivation level of Small business owners on the financial performance of their firms” With special reference to Gampaha District. - Kularathne, M.A.D.T.S.P. (IJRDO - Journal of Business Management, 2015)
Successful small business activity is important for a healthy economy and can be a major source of job creation. While the concept of entrepreneurship has been around for quite some time, researchers continue to explore the factors that underlie small business financial performance. Specifically, researchers have sought to further examine why some small ventures are more successful than others. The motivation has gained the attention of researchers and practitioners alike. Practitioners have realized that employees can no longer be perceived as biological machines that are capable of leaving their feelings, norms, and attitudes at home when they go to work. Researchers are embracing the motivation because of its relationship with efficiency, productivity, sales, and revenues, quality of service, customer loyalty, employee recruitment and retention and employee commitment. This study empirically examines the impact of motivation of small business owners on their financial performance. The results of the study showed that motivation is at high level and financial performance is at moderate level. The Pearson‟s correlation analysis indicated that there is a strong positive correlation between motivation and financial performance. The regression analysis indicated that there is a positive impact between motivation and financial performance. The implication of the finding is high level of motivation positively correlate with financial performance.